Modification of energy level diagram of nano-crystalline ZnO by its composites with ZnWO4 suitable for sunlight assisted photo catalytic activity. (March 2021) - Kale, Vaishali; Hunge, Y.M.; Kamble, Shalaka A.; Deshmukh, Madhuri; Bhoraskar, S.V.; Mathe, V.L.
Highlights: Synthesis of ZnO-ZnWO4 photocatalytic composite structure using thermal plasma route. Analysis of optical properties of the ZnO-ZnWO4 photocatalytic composite structure. Experimental measurements of work function of the composites using indigenous work function measurement set up. Analysis of sunlight activated photocatalytic response of the composites and its co-relation with optical properties. Abstract: In this paper we report single step synthesis of ZnO - ZnWO4 nanocomposites using thermal plasma route, where thermal plasma plume having sufficiently high thermal flux was impinged onto zinc -tungsten precursor and the species so evaporated were made to interact with oxygen in gas phase to get the final product. X-ray diffraction and Raman spectroscopic techniques were used to ascertain the composite phases. X-Ray Diffraction and Raman Spectroscopic analysis witnessed the formation of ZnO-ZnWO4 nano-composites, with monoclinic wolframite structure of tungstate while wurtzite structure of ZnO. Optical properties of the as synthesized product were recorded and analyzed using UV–vis and Photo-luminescence spectroscopic techniques. Retarding field diode method was used to determine work function of the ZnO-ZnWO4 composites under investigation, where gold sample was used as a reference. Subsequently, the photocatalytic efficiency of such ZnO-ZnWO4 nano-composites was analyzed by assessing the degradation of Crystal Violet dye. Experimentally measured values of surface work-function of the composites were analyzed and corelated with photocatalytic response. The degradation of Crystal Violet up to 82.07 % was achieved for 5 wt. % of W in the composite as compared to a value of 25.14 % for the pure ZnO nanoparticles under the exposure to sunlight radiations.